The Gratitude Opportunity Space: The timing of gratitude expressions in object passes - deSouza, Darcey K.; Park, Song Hee; Wei, Wan; Zhan, Kaicheng; Bolden, Galina B.; Hepburn, Alexa; Mandelbaum, Jenny; Mikesell, Lisa; Potter, Jonathan (Social Interaction. Video-Based Studies of Human Sociality, 2021)
This paper examines the situated use of expressions of gratitude and demonstrates how their precise timing matters for coordinating actions and managing relationships in social interaction. Focusing on activities that involve object passing, we introduce the concept of the gratitude opportunity space, a standard time for expressing gratitude. We explicate three discernable phases within the gratitude opportunity space for simple recruitment sequences involving an object pass (pre-delivery, on-delivery, and post-delivery positions) and explore how the gratitude opportunity space is dynamically recalibrated according to the activity underway in other activities that involve object passes (i.e., remote offers of objects and gift giving). Data are American and British English.